2022
DOI: 10.1111/ijfs.16151
|View full text |Cite
|
Sign up to set email alerts
|

Pearl millet protein hydrolysates exhibiting effective in‐vitro antioxidant, antidiabetic and anti‐lipidemic properties as potential functional food ingredient

Abstract: Millets are well-known for protein with high nutritional value and a range of health benefits. Milletderived proteins can thus be a rich source of bioactive peptides with multiple bioactive properties. In this study three proteolytic enzymes, i.e. alcalase, bromelain, and chymotrypsin were used to generate pearl millet protein hydrolysates (PMPHs) and explored for multifunctional bioactive properties. Degree of hydrolysis (DH) ranged between 28.69% and 59.21% with maximum DH observed for PMPs hydrolysed with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This could be due to cavitational waves that induce synergistic effects on the structural modifications in proteins, which leads to the exposure of buried active antioxidant sites within the protein structure and makes them more accessible for interactions with free radicals, like DPPH, compared to the parent protein . Also, the scavenging activity is aided by their abundance of amino acid peptide residues, which may transfer the electrons to free DPPH radicals at physiological pH and contribute to their antioxidant activities . In addition, US followed by protease hydrolysis can break the disulfide bonds in the protein, leading to the release of free SH groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This could be due to cavitational waves that induce synergistic effects on the structural modifications in proteins, which leads to the exposure of buried active antioxidant sites within the protein structure and makes them more accessible for interactions with free radicals, like DPPH, compared to the parent protein . Also, the scavenging activity is aided by their abundance of amino acid peptide residues, which may transfer the electrons to free DPPH radicals at physiological pH and contribute to their antioxidant activities . In addition, US followed by protease hydrolysis can break the disulfide bonds in the protein, leading to the release of free SH groups.…”
Section: Resultsmentioning
confidence: 99%
“…The bromelain-derived UBMPHs resulted in an increase in CEase inhibition activity as the sonication time increased from 5 to 15 min (IC 50 values = 0.54 to 0.34 mg/mL) but decreased after that; this might be due to the degradation of active peptides, which inhibit the CEase enzyme, and were unavailable to bind CEase active sites. Recently, previous studies reported that pearl millet hydrolysates 81 and amaranth protein hydrolysates 82 show higher CEase inhibition activity than intact protein. Moreover, Soares et al, 2015, 83 reported that the amaranth protein peptides showed inhibitors of HMG-CoA reductase, resulting in a hypocholesterolaemia effect.…”
Section: Antilipidemic Activity By Protein Hydrolysates 3521 Cease In...mentioning
confidence: 99%
See 2 more Smart Citations
“…The seed coat of millet contains the highest concentration of bioactive compounds, while the starchy endosperm has a relatively low concentration [ 8 , 9 ]. The extraction of bioactive compounds is an important process in food processing [ 10 ] as it allows for the isolation and concentration of compounds offering antioxidant and anti-inflammatory activities, which can help to reduce the risk of chronic diseases such as cancer, cardiovascular disease, and diabetes [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%